2002
DOI: 10.1089/152460902753668439
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Estrogen and Progesterone in Regulating Carbohydrate and Fat Utilization at Rest and during Exercise

Abstract: Understanding the role of the ovarian hormones in fat and carbohydrate metabolism during exercise may have practical applications in terms of understanding the metabolic consequences of amenorrhea, menopause, and hormone replacement therapy (HRT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 53 publications
0
45
1
1
Order By: Relevance
“…Animal studies have shown that in mature female rats, oestrogens have a powerful influence on substrate utilization during exercise (Tate & Holtz, 1998). Oestrogens are responsible for the shift of fuel oxidation away from carbohydrates towards fat by promoting lipid oxidation, which increases free fatty acid availability, while decreasing the rate of gluconeogenesis leading to carbohydrate sparing and decreased rate of glycogen use during exercise (D'Eon & Braun, 2002;Horton & Braun, 2004;Tarnopolsky, MacDougall, Atkinson, Tarnopolsky, & Sutton, 1990). As for the effect of testosterone, the hormone contributes to the "male" pattern of substrate use by reducing reliance on lipids and increasing the use of carbohydrates (Braun, Gerson, Hagobian, Grow, & Chipkin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that in mature female rats, oestrogens have a powerful influence on substrate utilization during exercise (Tate & Holtz, 1998). Oestrogens are responsible for the shift of fuel oxidation away from carbohydrates towards fat by promoting lipid oxidation, which increases free fatty acid availability, while decreasing the rate of gluconeogenesis leading to carbohydrate sparing and decreased rate of glycogen use during exercise (D'Eon & Braun, 2002;Horton & Braun, 2004;Tarnopolsky, MacDougall, Atkinson, Tarnopolsky, & Sutton, 1990). As for the effect of testosterone, the hormone contributes to the "male" pattern of substrate use by reducing reliance on lipids and increasing the use of carbohydrates (Braun, Gerson, Hagobian, Grow, & Chipkin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating E 2 level may play a significant role in substrate oxidation during exercise [10]. Several studies in rats [11][12][13][14] and in humans [15] have shown that E 2 supplementation influences substrate selection during endurance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that premenopausal women utilize fat to a greater extent and carbohydrate to a lesser extent than men during aerobic exercise at the same relative intensity [1][2][3][4][5][6][7][8][9]. This difference during aerobic exercise may reflect differences in estrogen concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ethics approval was obtained from the School of Biomedical Sciences Animal Ethics Committee, and all animal experimentation was conducted in accord with accepted standards of humane animal care. Under general anesthesia (20 mg/kg iv pentobarbital sodium and maintained with 1-2% isoflurane and oxygen), all animals were ovariectomized to avoid cyclic variations in plasma levels of ovarian hormones (10,28). At least 2 wk after ovariectomy, animals underwent a second surgery, also under general anesthesia (see Animals), where cannulas were inserted into one femoral artery.…”
Section: Analytical Techniquesmentioning
confidence: 99%